2019
DOI: 10.2147/dmso.s222066
|View full text |Cite
|
Sign up to set email alerts
|

<p>Serum CTRP3 Levels In Obese Children: A Potential Protective Adipokine Of Obesity, Insulin Sensitivity And Pancreatic β Cell Function</p>

Abstract: PurposeCTRP3 is a novel peptide that has recently emerged as an important regulatory adipokine of obesity and related metabolic disease. Little is known about its role in children. The current study aimed to investigate the potential role of CTRP3 in obese children and explore its relationships with insulin sensitivity, pancreatic β cell function, and obesity-related markers.Patients and methodsWe studied the levels of serum CTRP3 in 48 obese and 36 normal weight pre-puberty children. The levels of blood press… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
2

Citation Types

1
8
0

Year Published

2020
2020
2024
2024

Publication Types

Select...
6
1
1

Relationship

0
8

Authors

Journals

citations
Cited by 12 publications
(10 citation statements)
references
References 41 publications
1
8
0
Order By: Relevance
“…CTRP-3 concentrations were reduced to about 60% of baseline levels at study point V3 (three months after surgery or start of dietary intervention, respectively). Thus, systemic CTRP-3 appears to be down-regulated within the context of weight loss, a finding that was somewhat surprising due to the inverse relation of CTRP-3 levels and BMI known from the literature [13][14][15]. Reduction of body weight and BMI might have been expected to be accomplished by an increase of CTRP-3.…”
Section: Discussionmentioning
confidence: 91%
See 2 more Smart Citations
“…CTRP-3 concentrations were reduced to about 60% of baseline levels at study point V3 (three months after surgery or start of dietary intervention, respectively). Thus, systemic CTRP-3 appears to be down-regulated within the context of weight loss, a finding that was somewhat surprising due to the inverse relation of CTRP-3 levels and BMI known from the literature [13][14][15]. Reduction of body weight and BMI might have been expected to be accomplished by an increase of CTRP-3.…”
Section: Discussionmentioning
confidence: 91%
“…Therefore, CTRP-3 represents a putative regulatory element linking metabolism and inflammation ("metaflammation"). Similar to adiponectin, a negative correlation of systemic CTRP-3 levels with the occurrence of obesity and type 2 diabetes mellitus (T2D) has repeatedly been reported [13][14][15]. However, circulating levels were not affected in short term by an oral lipid load or during an oral glucose tolerance test in subjects from a cross-sectional study cohort [16].…”
Section: Introductionmentioning
confidence: 83%
See 1 more Smart Citation
“…As adipokines are involved in many critical physiological processes in the body, dysregulation of adipokines may lead to endocrine diseases ( 5 ). Additionally, research has shown that adipokines play an essential role in the pathogenesis of obesity and obesity-related diseases ( 6 ).…”
Section: Introductionmentioning
confidence: 99%
“…Therefore, abnormal changes in adipokines may also lead to some endocrine diseases in the body 5 . Besides, studies have shown that adipokines play an essential role in the pathogenesis of obesity and obesity-related diseases 6 .…”
Section: Introductionmentioning
confidence: 99%